The First Anti-Snakebite and Hepatoprotective Characterization of a Trypsin Kunitz-like Inhibitor (EcTI) from the Plant Enterolobium contortisiliquum; A Case of Two Soul Mates Meeting - Caroline R. C. Costa; Mariana N. Belchor; Airam Roggero; Laila L. Moraes; Ricardo Samelo; Isabelly Annunciato; Camila R. Bonturi; Maria L. V. Oliva; Sergio F. Sousa; Marcos A. de Oliveira; Marcos H. Toyama (Pharmaceuticals, 2023)
Snake venom serine protease (SVSP) interferes with the regulation and control of important biological reactions in homeostasis and can be classified as an activator of the fibrinolytic system and platelet aggregation. Our group has recently isolated a new serine protease from Crotalus durissus terrificus total venom (Cdtsp-2). This protein exhibits edematogenic capacity and myotoxic activity. A Kunitz-like EcTI inhibitor protein with a molecular mass of 20 kDa was isolated from Enterolobium contortisiliquum and showed high trypsin inhibition. Thus, the objective of this work is to verify the possible inhibition of the pharmacological activities of Cdtsp-2 by the Kutinz-type inhibitor EcTI. To isolate Cdtsp-2 from total C. d. terrificus venom, we used three-step chromatographic HPLC. Using the mice paw edema model, we observed an edematogenic effect, myotoxicity and hepatotoxicity caused by Cdtsp-2. In vitro and in vivo experiments showed that the alterations in hemostasis caused by Cdtsp-2 are crucial for the development of marked hepatotoxicity and that EcTI significantly inhibits the enzymatic and pharmacological activities of Cdtsp-2. Kunitz-like inhibitor may be a viable alternative for the development of ancillary treatments against the biological activities of venoms.